SpiceJet big sale offer : adding spice to air travel - Abhishek, (SAGE Knowledge. Cases., 2017)
SpiceJet came out with Big Sale offer in January 2013 in which the company offered 10 lakh air tickets for Rs. 2013 to travellers in Indian domestic civil aviation market. The promotion, aimed at increasing passenger load factor, generated wide publicity due to unprecedented nature of offer in highly competitive market. The case traces the history of promotions conducted by SpiceJet and examines the different aspects of promotion which become crucial while planning for promotions in service industry.